Cisplatin Desensitization in a Patient with Nasopharyngeal Carcinoma Experiencing Urticarial Allergic to Cisplatin - Doddy Rizqi Nugraha; Deshinta Putri Mulya; Susanna Hilda Hutajulu (Acta Interna The Journal of Internal Medicine, 2019)
Background. Allergic reactions to cisplatin are not uncommon situations with an incidence of 5-20%. In general, allergic reactions to cisplatin is a type 1 hypersensitivity with manifestations of itching, redness, papules, urticaria, chest pain, and anaphylactic symptoms. Desensitization methods are needed for patients who have no alternative medication.Case Report. A 59-year-old woman with nasopharyngeal carcinoma experienced urticaria because of cisplatin in her first cycle of chemotherapy. In the second cycle, chemotherapy desensitization program was applied using a 12-step Castell protocol. We measured vital signs and symptoms every 15 minutes. Administration of cisplatin was completed in 2 hours and the patient tolerated the whole program very well.Discussion. Risk factors of hypersensitivity to cisplatin include age <70 years, previous allergy history, history of carboplatin use with dose >650 mg, mutation of BRACA1/2 gene, and administration of combined regimens with taxane groups or liposomal inhibitor. Desensitization uses 3 solutions with 12 steps. Solution is 100 times the dilution of the target dose. Solution 2 is 10 times the dilution of the target dose and solution 3 uses the appropriate target dose. Each solution is administered for 15 minutes using an infusion pump. Strict monitoring of vital signs and patient symptoms are done every 15 minutes during the program.Conclusion. Doctors should be aware of allergies to cisplatin. Currently, the allergic reaction to cisplatin can be overcome using the desensitization method when no alternative drug is not available.